Farmer field schools for improving economic sustainability performance of Indonesian vegetable production. Issue 4 (28th December 2020) - Mariyono, Joko; Dewi, Hanik Anggraeni; Daroini, Putu Bagus; Latifah, Evy; Hakim, Arief Lukman; Luther, Gregory C.
Abstract : Purpose: A research and development project disseminated ecological technologies to approximately 3, 250 vegetable farmers through farmer field schools (FFS) in four districts of Bali and East Java provinces of Indonesia. This article aims to assess the economic sustainability of vegetable production after FFS participation. Design/methodology/approach: A survey randomly sampled 500 farmers, comprised of FFS participants (50%) and non-FFS participants (50%). Based on 1, 000 farm operations, this analysis employed input-saving technology as the fundamental model examined using the double-difference method. Simultaneous reduction of agrochemicals and improvement of productivity represent indicators of economic sustainability. Findings: Results indicate that pesticide use decreased without jeopardising farm productivity; moreover, vegetable production increased. These findings indicate that the ecological technologies transferred through FFS significantly improved economic sustainability performance. Research limitations/implications: This study purposively selected farmers who grew tomato and chilli. Thus, the outcomes are not generalisable to other crops. Practical implications: FFS continues to be an effective method for transferring agricultural technologies to farmer communities. Policymakers are recommended to use FFS for disseminating beneficial and sustainable technologies to broader agricultural communities. Social implications: The adoption of ecological technologies provides positive economic and ecological milieus. Originality/value: This study employs a double-differences approach to verify input-saving technological progress. Therefore, the performance of economic sustainability attributable to the project intervention is theoretically justified.